Eggshell/TiO2 Composite for Palm Oil Mill Secondary Effluent Treatment - Yahya, Nur Aqilah; Mazlan, Nadia Asyiqin; Abd Khalid, Nur Hafizah; Hairom, Nur Hanis Hayati (Multidisciplinary Applied Research and Innovation, 2021)
The integration of eggshell and titanium dioxide composite for treating palm oil mill secondary effluent (POMSE) was studied. This study is focusing on the effectiveness of the eggshell/titanium dioxide (ES/TiO2) composite for adsorption capacity and photocatalytic process. Five samples of ES/TiO2 composite were synthesized and compared with two control samples which are 100% TiO2 and eggshell. The amount of TiO2 catalyst loading was investigated, followed by the different ratios of ES/TiO2 for POMSE removal. The result showed 1 g/mL of TiO2 loading gives the higher performance of adsorption and photocatalytic performance compared to others. Referring to this loading, the optimum integration ratio of ES/TiO2 composite was at 6:4 where the adsorption and photocatalytic performance was achieved 90%. It is believed that this integrated approach can be implemented in the industry in order to achieve a discharged standard of POMSE and helps to save the nature and environment so as not to be contaminated in the future.